SIMBOL NARKOBA DALAM LAGU-LAGU HARRY STYLES: ANALISIS MELALUI ‘NEGOTIATED READINGS' - W, Ardito Kenanya Hudson; Kurniawan, Yohanes; Kurniawan, Yulius (Seminar Nasional Ilmu Terapan, 2024)
This study delves into the use of drug symbols in Harry Styles' songs and explores the meanings attributed to these symbols through the lens of John Fiske's 'Negotiated Readings' theory. The research adopts a qualitative descriptive method to examine how audiences negotiate and interpret drug symbols in Styles' lyrics, focusing on three key themes. First, the analysis reveals that drug symbols are utilized to convey intense emotional pain, drawing parallels to the struggles of addiction in songs such as 'Meet Me In The Hallway'. Second, the study uncovers how drug symbol antidotes symbolize remedies or counteractions, depicting love as a healing force rather than a destructive one in tracks like 'Golden' and 'Daylight'. Lastly, the research highlights how drug symbols are employed to depict struggles and challenges within relationships, evident in songs like 'As It Was' and 'Daylight'. By applying the theory of 'Negotiated Readings' to the analysis of drug symbols in Harry Styles' songs, this study contributes to a deeper understanding of how audiences interpret and engage with symbolic meanings in popular music.